2021
DOI: 10.3389/fmed.2021.616355
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Ambient Air Pollution and Myocardial Infarction: A Systematic Review and Meta-Analysis

Abstract: Background and Objective: An increasing number of epidemiological original studies suggested that long-term exposure to particulate matter (PM2.5 and PM10) could be associated with the risk of myocardial infarction (MI), but the results were inconsistent. We aimed to synthesized available cohort studies to identify the association between ambient air pollution (PM2.5 and PM10) and MI risk by a meta-analysis.Methods: PubMed and Embase were searched through September 2019 to identify studies that met predetermin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Both results are also comparable with what has been recently published in reviews and meta‐analyses. 50 , 51 The 10% increase in total mortality for PM 2.5 is also similar to what was previously found using the same DID method 46 and among Medicare beneficiaries in the United States. 52 …”
Section: Discussionsupporting
confidence: 84%
“…Both results are also comparable with what has been recently published in reviews and meta‐analyses. 50 , 51 The 10% increase in total mortality for PM 2.5 is also similar to what was previously found using the same DID method 46 and among Medicare beneficiaries in the United States. 52 …”
Section: Discussionsupporting
confidence: 84%
“…Air pollution could also be related to COVID-19 disease through its contribution to chronic conditions that increase susceptibility to more severe COVID-19 disease (Williamson et al 2020). Long-term exposure to air pollution has been linked to incident diabetes (Zou et al 2021), as well as cardiovascular (Yang et al 2020) and chronic respiratory (Park et al 2021) and neurodegenerative disease (Power et al 2016). Owing to sample size limitations, we were not able to quantify the mediating role of these conditions in the air pollution-COVID-19 disease relationship.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Cesaroni et al demonstrated a 12% and 13% escalation, respectively, in the risk of acute coronary diseases due to chronic exposure to PM 10 and PM 2.5 [ 37 ]. The scientific literature consistently highlights a more detrimental impact of PM 2.5 compared to PM 10 on human health [ 20 , 33 ], attributed to its larger surface area facilitating increased absorption of chemical constituents and its extended persistence in ambient air, enhancing its capability to reach pulmonary alveoli [ 20 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations consistently highlight that exposure to air pollutants, whether over short or long periods, significantly contributes to negative outcomes in cardio-respiratory conditions [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Earlier epidemiological discoveries specifically emphasize the heightened detrimental effects of PM on CVD compared to other airborne pollutants, especially in cases of increased exposure to PM 2.5 [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%